Symbiont Community Changes Confer Fitness Benefits for Larvae in a Vertically Transmitting Coral - Daniel Olivares‐Cordero; Courtney Timmons; Carly D. Kenkel; Kate M. Quigley (Ecology and Evolution)
ABSTRACT Coral reefs worldwide are threatened by increasing ocean temperatures because of the sensitivity of the coral‐algal symbiosis to thermal stress. Reef‐building corals form symbiotic relationships with dinoflagellates (family Symbiodiniaceae), including those species which acquire their initial symbiont complement predominately from their parents. Changes in the composition of symbiont communities, through the mechanisms of symbiont shuffling or switching, can modulate the host's thermal limits. However, the role of shuffling in coral acclimatization to heat is understudied in coral offspring and to date has largely focused on the adults. To quantify potential fitness benefits and consequences of changes in symbiont communities under a simulated heatwave in coral early life‐history stages, we exposed larvae and juveniles of the widespread, vertically transmitting coral, Montipora digitata, to heat stress (32°C) and tracked changes in their growth, survival, photosynthetic efficiency, and symbiont community composition over time relative to controls. We found negative impacts from warming in all fitness‐related traits, which varied significantly among larval families and across life‐history stages. Larvae that survived heat exposure exhibited changes in symbiont communities that favored symbionts that are canonically more stress tolerant. Compared to larvae, juveniles showed more rapid mortality under heat stress and their symbiont communities were largely fixed regardless of temperature treatment, suggesting an inability to alter their symbiont community as an acclimatory response to heat stress. Taken together, these findings suggest that capacity for symbiont shuffling may be modified through ontogeny, and that the juvenile life stage may be less flexible and more at risk from climate warming in this species.